A roadmap toward implementing health technology assessment in Egypt - Fasseeh, Ahmad Nader; Elezbawy, Baher; Gamal, Mary; Seyam, Ahmed; Abourawash, Asmaa; George, Mohsen; Anwar, Mohamed; Amin, Magdy; Khalifa, Ahmed Yehia; Elshalakani, Amr; Hatem, Ashraf; Abdelhamid, Sohir; et al. (Frontiers in Public Health, 2022)
Background The Egyptian healthcare system is currently in the early phases of health technology assessment (HTA) implementation. The aim of this study is to propose an implementation roadmap based on the national healthcare system status. Methods A survey was conducted among Egyptian healthcare sector decision-makers to assess the current and future (preferred) HTA implementation status in Egypt based on a widely used international scorecard methodology. As a second step interviews were conducted with a diverse group of middle and top tier management in the Egyptian health care system to interpret survey results and make recommendations for specific actions. Results Experts recommended more capacity building programs for HTA and health economics. They also propose establishing HTA units in separate healthcare authorities and merging them into a single central HTA unit in the long term. Concerning scope of implementation, experts recommended starting by assessing innovative pharmaceuticals then expanding the scope to cover all health technologies in the long term. They also recommended using innovative tools like "multi-criteria decision analysis (MCDA)" for tendering and "managed entry agreements" for reimbursement decisions. Local burden of diseases and costing studies are recommended to facilitate the implementation of HTA. Conclusion National experts agreed that several actions are vital for the success of HTA implementation in Egypt, including coordination between HTA bodies, application of an explicit MCDA framework, and strengthening local evidence generation. To implement these actions, investment in technical capacity building is indispensable. Most of the experts were in favor of using multiple and soft cost-effectiveness thresholds. Efforts should be done to publish HTA submission guidelines and timelines of the processes.